"O morir en la porfía o ser conde de Belflor”: Teodoro's ambition in Lope de Vega and Pilar Miró (Ogigia. Revista Electrónica de Estudios Hispánicos, 2016)
Each approach to El perro del hortelano (1613), by Lope de Vega, reveals new nuances of the main male character. The well-known figure of Teodoro, the secretary of the countess Diana de Belflor, resists any taxonomy and reveals itself as a subtle character, with doubts and contradictions. His psychological depth clearly shows through his ambition and careerism, features that form his complex personality. Through the detailed analysis of the main features that characterise Teodoro in this comedia and in the film adaptation by Pilar Miró (1996), this paper aims at unfolding how and why Pilar Miró reshaped the personality of Teodoro in her cinematographic version.
Keywords: Lope de Vega; El perro del hortelano; Pilar Miró; Teodoro; film adaptation